2019
DOI: 10.1002/advs.201801927
|View full text |Cite|
|
Sign up to set email alerts
|

ATG7 Promotes Bladder Cancer Invasion via Autophagy‐Mediated Increased ARHGDIB mRNA Stability

Abstract: Since invasive bladder cancer (BC) can progress to life threatening metastases, understanding the molecular mechanisms underlying BC invasion is crucial for potentially decreasing the mortality of this disease. Herein, it is discovered that autophagy‐related gene 7 (ATG7) is remarkably overexpressed in human invasive BC tissues. The knockdown of ATG7 in human BC cells dramatically inhibits cancer cell invasion, revealing that ATG7 is a key player in regulating BC invasion. Mechanistic studies indicate that MIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 47 publications
2
45
0
Order By: Relevance
“…The results from the present study discovered that MIR516A targeted 3ʹ-UTR of PHLPP2 mRNA, which downregulates its protein translation in human BC; therefore, we defined the novel mechanism of MIR516A regulating PHLPP2 protein translation. Due to the complexity of autophagy, it has been shown to function as a double-edged sword that either protect or suppress human bladder cancer, depending on the stimuli of autophagy, the stage of cancer, and the downstream mediators or effectors [47,48]. Our recent studies have shown that autophagic responses mediated by SESN2/Sestrin 2 mainly result in autophagic inhibition of human bladder cancer cells [48], whereas ATG7-mediated autophagic responses promote growth and invasion of human bladder cancer cells [47].…”
Section: Discussionmentioning
confidence: 99%
“…The results from the present study discovered that MIR516A targeted 3ʹ-UTR of PHLPP2 mRNA, which downregulates its protein translation in human BC; therefore, we defined the novel mechanism of MIR516A regulating PHLPP2 protein translation. Due to the complexity of autophagy, it has been shown to function as a double-edged sword that either protect or suppress human bladder cancer, depending on the stimuli of autophagy, the stage of cancer, and the downstream mediators or effectors [47,48]. Our recent studies have shown that autophagic responses mediated by SESN2/Sestrin 2 mainly result in autophagic inhibition of human bladder cancer cells [48], whereas ATG7-mediated autophagic responses promote growth and invasion of human bladder cancer cells [47].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that autophagy is an important mechanism of tumorigenesis and that interfering with autophagy signaling by targeting key ARGs may be a novel therapeutic strategy for cancer treatment. Previously, researchers have confirmed that four ARGs, including hypoxia inducible factor-1 (HIF-1α), autophagy-related 7 (ATG7), sestrin 2 (SENS2), and beclin 1 (BECN1), were associated with the cell proliferation, apoptosis and invasion of BUC cells (28)(29)(30)(31). However, the potential clinical value of ARGs for the prognosis of patients with BUC remains unclarified.…”
Section: Discussionmentioning
confidence: 99%
“…BECN1 affects the drug sensitivity of OS cells by mediating the autophagy process [43]. ATG12 is involved in osteosarcoma cell metastasis [44], and ATG7 is associated with the invasiveness of bladder cancer cells [45]. The expression level of PIK3C3 in breast cancer gradually increases with disease progression [46], and low expression of GABARAPL1 is associated with poor prognosis in patients with breast cancer and hepatocellular carcinoma [47,48].…”
Section: Discussionmentioning
confidence: 99%